Penerapan Metode Gray Level Co-Occurrence Matrix dalam Mengklasifikasi Tingkat Kematangan Buah Naga Berbasis Citra - Folla, Marni Monika; Bulan, Semlinda Juszandri (J-Icon : Jurnal Komputer dan Informatika, 2023)
Dragon fruit, also known as pitaya, is a fruit that originates from cactus plants belonging to the genus Hylocereus and Selenicereus, in the Cactaceae family, Cactaes order, and Dicotyledonae class. Dragon fruit is highly popular among people due to its various health benefits. The maturation process of dragon fruit begins approximately 11 months after planting, and it takes about 50 to 55 days from the formation of the flower bud to the fruit being ready for harvest. The maturation process of dragon fruit starts approximately 11 months after planting. From the moment the flower bud is formed until the fruit is ready to be harvested, it takes about 50 to 55 days. Dragon fruit has different levels of maturity, namely raw, half-ripe, ripe, and overripe. These maturity levels can be identified through changes in the fruit skin color. Currently, farmers still manually sort dragon fruit by directly observing the fruit's surface, but this method often leads to inaccurate and inconsistent classifications due to human error. Therefore, researchers are striving to develop a system that can classify the maturity levels of dragon fruit by utilizing Hue Saturation Value (HSV) color characteristics and implementing the Gray Level Co-Occurrence Matrix (GLCM) method. In the classification system developed using Matlab software, there are four maturity categories for dragon fruit, including raw, half-ripe, ripe, and overripe. This research achieved the highest accuracy of 90%. A total of 100 datasets were used, by using 5-fold-cross validation. Data analysis was performed using the GLCM method by calculating the nearest distance between each training and testing data using the Euclidean distance formula.